Impact of separator efficiency and removed solids moisture content on make-up water requirements for sand recovery - Joseph P. Harner; John F. Smith; Michael J. Brouk (Kansas Agricultural Experiment Station Research Reports, 2007)
Separator efficiency and moisture content of separated solids influence the make-up water requirements on a dairy seeking to utilize recycled water for sand reclamation. Additional water requirements range from 0 to 79 gallons/cow per day depending on the efficiency of the solid to liquid separation process. Make-up water includes any water stored in a containment structure, excluding urine. Final moisture content of the separated solids had marginal impact on the additional water requirements.; Dairy Day, 2007, Kansas State University, Manhattan, KS, 2007; Dairy Research, 2007 is known as Dairy Day, 2007
Keywords: Dairy Day; 2007; Kansas Agricultural Experiment Station contribution; no. 08-127-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 984; Dairy; Sand recovery; Recycled water; Separator efficiency